Analysis of Student Response to the Utilizing of LMS in Applied Physics Course Post Covid-19 Pandemic - Citra Dewi, Yunita (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
A study on the analysis of student response to using POLBAN's LMS E-Learning in the Applied Physics course post the Covid-19 pandemic has been conducted. This research aims to determine the extent of student acceptance and enthusiasm in utilizing the LMS after face-to-face classes are reintroduced. The research is categorized as qualitative descriptive research. The research method involved distributing questionnaires to 107 students taking the Applied Physics course from the Chemical Analyst and Mechanical Engineering study programs at the Bandung State Polytechnic during the odd semester of the academic year 2022/2023. The questionnaire responses were processed by calculating the total average scores for each question. Based on the interval scale analysis of acceptance ratings, the research findings indicate that the level of student acceptance towards using E-Learning in the Applied Physics course posts during the Covid-19 pandemic falls under the " Accepted " category. It is evident from calculating the overall average score for all statements, which amounts to 403.17 points out of 535 points. Therefore, it can be concluded that utilizing LMS in face-to-face classes is still highly suitable as a support and companion for post-Covid-19 pandemic teaching.